Necessity of improvement of foreign language teaching in the Slovak Republic - Šarvajcová, Marcela; Štrbová, Monika (Journal of Education Culture and Society, 2021)
Aim. The aim of the research study was to investigate the opinions of the Slovakian secondary school foreign language teachers and learn about their views on the system of education in the field of enhancement of teachers` professional qualifications. Methods. To perform the results of the study the method of focus group was used. Results. The results of the presented research show the differences between the perception of foreign language education in the past and how it appears today through the views of selected number of foreign language teachers in Slovakia. The pivotal role is played by the technological skills of the students and their ability to use information technologies instructed in foreign languages. The research results also indicate the possibilities of teachers to get in direct contact with the target foreign language as a part of their professional development. The research participants also specified the factors that they considered the most influential in the process of foreign language learning. Conclusion. The purpose of the article is to discuss the urge to achieve highly professional foreign language education in today`s technological society. As shown by the results obtained from the focus group, the teachers/participants agreed on a single highly impactful factor: family.